Visual Outcomes and Prognostic Factors of Large Submacular Hemorrhages Secondary to Polypoidal Choroidal Vasculopathy - Matsuo Y (Dove Medical Press, 2021)
Yu Matsuo,1 Masatoshi Haruta,1 Yumi Ishibashi,1 Koki Ishibashi,1 Kei Furushima,1 Nobuhiro Kato,1 Kenta Murotani,2 Shigeo Yoshida1 1Department of Ophthalmology, Kurume University School of Medicine, Kurume, Japan; 2Biostatistics Center, Kurume University, Kurume, JapanCorrespondence: Masatoshi HarutaDepartment of Ophthalmology, Kurume University School of Medicine, 67 Asahi-machi, Kurume, Fukuoka, 830-0011, JapanTel +81 942 31 7574Fax +81 942 37 0324Email haruta_masatoshi@med.kurume-u.ac.jpPurpose: Patients with polypoidal choroidal vasculopathy (PCV) may develop large submacular hemorrhages (SMHs), which may result in severe visual loss. This study was performed to determine the visual outcomes and prognostic factors of large SMHs secondary to PCV.Patients and Methods: We retrospectively reviewed the medical records of patients diagnosed with PCV who developed a large SMH. The best-corrected visual acuity (BCVA) data were collected at the SMH development, 1 month, 1 year after the SMH development, and at the final visit. Patients’ medical information also were collected and included age, gender, systemic hypertension, current regular use of an anticoagulant or antiplatelet medication, the initial area of the SMH, breakthrough vitreous hemorrhage, ocular treatment, and fellow eye status. Univariate and multiple regression analyses were performed to determine the prognostic factors for the BCVA 1 year after the development of large SMHs.Results: Thirty eyes of 29 patients were included in this study. The mean area of the SMHs at the development was 17.0 disc areas. The mean follow-up period after the development of SMHs was 53.5 months. The mean BCVA at the development, 1 month, and 1 year after the development, and at the final visit were 20/151, 20/263, 20/138, and 20/152, respectively. Multiple regression analyses indicated that a SMH 20 disc areas or larger was a significant negative factor, and the BCVA 1 month after the development was a significant positive factor affecting the BCVA 1 year after the development of large SMHs.Conclusion: The increase in the initial area of SMH was correlated inversely with the BCVA 1 year after the development of SMH. The BCVA 1 month after the development may predict the BCVA 1 year after the development of a large SMH.Keywords: anti-vascular endothelial growth factor therapy, indocyanine green angiography, multiple regression analyses, optical coherence tomography, pneumatic displacement